Study of Enhancing Sludge Anaerobic Fermentation Performance by Nano Zero-valent Iron Synergized with Sodium Percarbonate - JIN Baodan; JIA Yusheng; DENG Weiling; GU Jiayu; WANG Jiacheng; LIU Ye; WANG Baogui; JI Jiantao (工程科学与技术)
ObjectiveWaste-activated sludge (WAS) is a by-product of wastewater treatment plants (WWPTs), which seriously affects the operation of WWPTs and environmental safety. WAS is rich in protein, polysaccharides, and other macromolecular organic matter, but it also contains a significant amount of heavy metals and viruses. If not effectively treated, it causes severe secondary pollution in the environment and results in the waste of resources. The reduction, stabilization, harmlessness, and recycling of residual sludge represent the most critical challenges in sludge management. Anaerobic fermentation of sludge is the most common technology for treating and disposing of WAS, achieving the goals of sludge reduction and recycling. This study investigates the feasibility of nano zero-valent iron (nZVI) synergized with sodium percarbonate (SPC) to enhance the anaerobic fermentation performance of sludge using WAS from a municipal WWTP, and it also reveals the underlying fermentation mechanism. In addition, the optimal fermentation condition is identified.MethodsThe Fe2+ and Fe3+ derived from the hydrolysis of nZVI cooperated with the H2O2 produced by SPC to establish Fenton or Fenton-like systems. In addition, Fe3+ was reduced to Fe2+ by nZVI, establishing a cyclic reaction system that extended its action time within the fermentation system, enhancing the fermentation performance. In addition, Fe2+ and Fe3+ acted as catalysts to raise the decomposition of H2O2, resulting in the generation of many hydroxyl radicals (<alternatives>H<msubsup>O·</msubsup> <?fx-imagestate width="5.33400011" height="3.13266683"?> <?fx-imagestate width="5.33400011" height="3.13266683"?> </alternatives>, which oxidized and degraded organic matter and increased the sludge fermentation performance. In addition, Fe2+ reacted with PO<alternatives><msubsup>43‒</msubsup> <?fx-imagestate width="2.11666679" height="3.55599999"?> <?fx-imagestate width="2.11666679" height="3.55599999"?> </alternatives>‒P to produce Fe3(PO4)2•8H2O precipitation, recovered PO<alternatives><msubsup>43‒</msubsup> <?fx-imagestate width="2.11666679" height="3.55599999"?> <?fx-imagestate width="2.11666679" height="3.55599999"?> </alternatives>‒P from the fermentation system, and evaluated the phosphorus removal performance of the SPC-enhanced nZVI fermentation system. Therefore, the fermentation mechanism was studied through batch experiments. A 2.5 L plexiglass reactor was used, and a magnetic stirrer was employed to maintain uniform stirring speed. The reaction temperature was room temperature (20~25 ℃), and the pH was not adjusted. A volume of 2.0 L of concentrated sludge was added to the F0~F3 reactors. The optimal dosage of SPC was determined to be 0.2 g SPC/g SS. Thus, the dosage of additives was set as follows: F0 (0.2 g SPC/g SS), F1 (0.2 g SPC/g SS + 10 mg nZVI/g SS), F2 (0.2 g SPC/g SS + 20 mg nZVI/g SS), and F3 (0.2 g SPC/g SS + 30 mg nZVI/g SS). In order to explore the influence of nZVI and SPC on the hydrolysis and acidification processes of the entire anaerobic fermentation system, the experiment involved a one-time addition of nZVI and SPC to the fermentation system without subsequent supplementation.Results and DiscussionsThe results showed that nZVI synergized with SPC has a significant effect on the hydrolytic acidification performance of the WAS anaerobic fermentation system. The protein concentration first increased and then decreased with nZVI addition, while polysaccharides increased with nZVI addition. The maximum concentrations reached 314.43 mg COD/L for protein and 140.14 mg COD/L for polysaccharides, respectively. This demonstrated that the Fenton system or Fenton-like system can facilitate the degradation of macromolecular organic matter. The short-chain fatty acids (SCFAs) concentrations first increased and then decreased with nZVI, with the maximum SCFAs observed in the F3 fermentation system at 1214.24 mg COD/L. The percentage of acetic acid content in the F3 fermentation system was also the highest, at 61.49%. These findings indicated that nZVI combined with SPC enhances the acidification performance of the fermentation system. Compared to the other three fermentation systems, the hydrolysis products of nZVI, Fe2+can react with PO<alternatives><msubsup>43‒</msubsup> <?fx-imagestate width="2.11666679" height="3.55599999"?> <?fx-imagestate width="2.11666679" height="3.55599999"?> </alternatives>‒P to form ferrous phosphate Fe3(PO4)2 precipitate, resulting in a marked decrease in PO<alternatives><msubsup>43‒</msubsup> <?fx-imagestate width="2.11666679" height="3.55599999"?> <?fx-imagestate width="2.11666679" height="3.55599999"?> </alternatives>‒P concentration. The lower PO<alternatives><msubsup>43‒</msubsup> <?fx-imagestate width="2.11666679" height="3.55599999"?> <?fx-imagestate width="2.11666679" height="3.55599999"?> </alternatives>‒P concentration also indicated an improvement in the fermentation conditions. nZVI has a remarkable influence on biological enzymes in the synergized fermentation system, where the protease activity first increased and then declined, with the highest protease activity found in the F1 fermentation system (0.2 g SPC/g SS + 10 mg nZVI/g SS). However, the activities of α-glucosidase, acetic acid kinase, butyric acid kinase, dehydrogenase, and superoxide dismutase increased with nZVI addition. In contrast, the activities of ALP and ACP decreased with the increase in nZVI concentration. This indicated that nZVI combined with SPC enhances the oxidation performance of the fermentation system, and the higher oxidation level reduces enzyme activity. At the same time, the nZVI synergized SPC sludge fermentation system raises the enrichment of microbial functions, including Firmicutes, Bacteroidota, Proteobacteria, Actinobacteriota, Chloroflexi, and other bacteria such as Proteiniclasticum, Christensenellaceae_R-7, Petrimonas, and Macellibacteroides, which ensure effective hydrolysis and acidification performance and efficiently achieve SCFAs accumulation.ConclusionsThe results showed that the cooperation of nZVI with SPC significantly improved the anaerobic fermentation performance of WAS. This collaboration effectively accelerated the degradation of macromolecular organic matter in the fermentation system, providing a readily available substrate to produce SCFAs, particularly acetic acid. In addition, nZVI, in conjunction with SPC, contributed to the removal of phosphorus from the fermentation system, facilitating the recovery of phosphorus as a ferrous phosphate precipitate. The enrichment of functional bacteria further ensured the efficient hydrolysis and acidification performance of the nZVI‒SPC collaborative sludge fermentation system. The F3 fermentation system, with 0.2 g SPC/g SS + 30 mg nZVI/g SS, represented the optimal fermentation condition. This finding provides a new perspective and theoretical foundation for expanding sludge treatment and disposal methods.